The Epidemic - Young, Suzanne (Young, Suzanne. Program series., 2016)
"After discovering that everything she's ever known including her own identity has been a lie, Quinlan McKee is determined to find out the truth about her past. But in her search for answers, she discovers a cover-up more chilling than she can imagine. An epidemic is coming, and there's no way to stop it"--